European railway deregulation: the influence of regulatory and environmental conditions on efficiency - Heike Wetzel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
The objective of this paper is to analyze the impact of regulatory and environmental conditions on technical efficiency of European railways. Using a panel data set of 31 railway firms from 22 European countries from 1994 to 2005, a multioutput distance function model, including regulatory and environmental factors, is estimated using stochastic frontier analysis. The results obtained indicate positive and negative efficiency effects of different regulatory reforms. Furthermore, estimating models with and without regulatory and environmental factors clearly indicates that the omission of environmental factors, such as network density, substantially changes parameter estimates and, hence, leads to biased estimation results.
Keywords: L92; L51; L22; 330; European railways; technical efficiency; stochastic frontier analysis; Schienenverkehr; Deregulierung; Umweltpolitik; Wirtschaftspolitische Wirkungsanalyse; Eisenbahngesellschaft; Technische Effizienz; Stochastischer Prozess; Schätzung; EU-Staaten